Construction and optimization of ecological security patterns in ecologically fragile areas: a case study of Lanzhou City, China - Dong, Jianhong; Li, Lina; Yang, Wenjin; Liu, Benteng; Zhang, Xinhong (Frontiers in Environmental Science, 2025)
IntroductionUnder China’s strategic initiative for ecological conservation and high-quality development in the Yellow River Basin, establishing Ecological Security Patterns (ESPs) has emerged as a crucial approach to reconcile ecological preservation with socioeconomic growth.MethodsThis paper takes Lanzhou city in the upper reaches of the Yellow River Basin in China as an example. First, we employed the InVEST-HQ module to assess habitat quality and extract the ecological sources. Second, we constructed resistance surfaces reflecting the expansion dynamics of ecological and urban sources. Third, the Minimum Cumulative Resistance (MCR) model, GIS Hydrological Analysis module and Spatial Analysis module were used to divide ecological suitability zones, determine ecological corridors, and identify ecological nodes, so as to construct ESPs and propose optimization strategies.ResultsThe results showed as follows: 1 Spatial differentiation of ecological sources (1388.73 km2, 10.61%) predominantly in northwestern and southern regions, contrasting with urban sources (527.66 km2, 4.03%) concentrated along the Yellow River Valley and Qinwangchuan Basin; 2 According to the MCR difference between ecological sources and urban sources, the study area was divided into ecological core zone (ECZ), ecological buffer zone (EBZ), optimized construction zone (OCZ), and suitable construction zone (SCZ), with the proportions of 37.05%, 25.68%, 18.53% and 18.74%, respectively; 3 Based on the theory of “matrix - patch - corridor - node” in landscape ecology, the ESPs of Lanzhou City was constructed with the framework of “One belt, Two rings, Four screens, Six districts and multiple corridors”.DiscussionThe results can provide reference for ecological environment protection and ecosystem restoration in the upper reaches of the Yellow River Basin in China.